1. The problem statement, all variables and given/known data the substitution x=es, y=et converts f(x,y) into g(s,t) where g(s,t)=f(es, et). If f is known to satisfy the partial differential equation x2(d2f/dx2) + y2(d2f/dy2) + x(df/dx) + y(df/dy) = 0 show that g satisfies the partial-differential equation (d2g/ds2) + (d2g/dt2) = 0 3. The attempt at a solution I feel like this is a simple problem - All I need to figure out is how to find the partial derivative of f(x,y) and the double partial derivative, but I'm not sure how to do it. Are the values of x and y relevant for the first part of the question? what would df/dx be? D1f(x,y) = (y)f'(x,y) by the chain rule? and similarly df/dy = D2f(x,y) = (x)f'(x,y)? Someone please help!